Solusi Untuk Mengatasi Kesulitan Pembelajaran Bahasa Jepang Secara Daring di SMAN 2 Temanggung - Nian Prastika Adhani; Ai Sumirah Setiawati; Yuyun Rosliyah; Heni Hernawati (Program Studi Sastra Jepang, Universitas Komputer Indonesia Bandung, 2023)
This study was conducted to describe the difficulties of SMAN 2 Temanggung students in facing online Japanese learning during the Covid-19 pandemic and then find out the causes so that researchers can provide solutions. This study uses a quantitative descriptive method. The research sample was the entire population, namely 81 students from class XII IPA and XII IPS of SMA Negeri 2 Temanggung who participated in online Japanese language learning. Data was obtained through a questionnaire containing 4 indicators with 24 questions. The scale used is a Likert scale with an interval of 1-4. The validity of the research instrument was carried out with content validity and the reliability of the instrument was calculated using the Cronbach Alpha formula through the SPSS application. The data analysis technique was carried out using the percentage scale guideline model and the interpretation classification of the number of percentage answers according to Arikunto. Based on the results of the study, the average percentage was 56.21% which showed that more than half of XII IPA and XII IPS students had difficulty learning Japanese online. These difficulties are technical difficulties, difficulties when learning Japanese online takes place, difficulties in doing assignments and difficulties from the environment.